Socialisation of Medicine (1930)
1930 1930 1930s 2 pages Constructive SOCIALISATION OF MEDICINE. Independent Labour Party Resolution. Easter 1930 "That realising that the interests of the sick and the health of the workers will only be maintained by a Socialist State, and whilst working for this object, the Conference believes that it is necessary to specially organise the workers for the socialization of medicine and the medical workers and services, and form a Workers' National Health and Sickness Committee, which should necessarily have a democratic and socialistic, scientific and representative basis, its objects being to promote : "1. The interests of the sick fully in all directions, including their adequate financial support during illness. "2. The efficient and scientific, adequate and humane, medical and institutional treatment, diagnosis, care, and after-care of all sick, injured, and infirm. "3. Such measures as would tend to prevent sickness, accidents, and injuries, and to give a healthy life to the workers." The Conference asked the I.L.P. and the N.A.C. to formulate a national health policy for the socialization, which includes the humanization, unification, nationalisation and rationalisation of medicine. 1. Proposing the resolution, Dr. Bushnell said medicine included at present (1) sick workers, who produced the raw material for this basic and key industry; (2) the medical, midwifery, maternity, dental, nursing, pharmaceutical, health, sanitary, and all allied medical workers; (3) the Central Government Departments (medical, health, and sickness insurance), viz., the Ministries of Health and Education, the Home Office, the Board of Control, Registrar-General, and others; (4) the Local Government Departments, as health, public assistance, and education (medical), maternity and child welfare, mental, sanitary, etc., committees; also approved societies. These would be unified and socialised. 2. The sick under Socialism would be served by unified medical and allied services of the Ministry of Health, paid an adequate living income, with an incentive to service, and not to profit from the exploitation of sickness of the present commercialised and capitalistic system. 3. The authority of medical science would be confined solely to its own sphere, where it would be unquestioned. 4. The service and its institutions would be free and open to all sick, adequate in numbers and accommodation, efficient in qualifications (specialist) and modem equipment, affording the highest and most up-to-date treatment. 5. The medical and allied workers would be trained by their curriculum to be social servants, teachers, missionaries of health and practitioners of preventive as well as curative medicine. 1 292/840/1/25